Intercalation events visualized in single microcrystals of graphite - Edward R. White (Nature Portfolio, 2017)
The common lithium-ion battery is re-charged by intercalating its graphite anode, but intercalation remains not well understood. Electron microscope video of intercalating graphite microcrystals reveals that the charge transfer occurs in current pulses that do not match theoretical expectations.